On fourteen species of Euochin Prószyński, 2018 from China (Araneae: Salticidae: Euophryini) - Wang, Weihang; Zhang, Junxia (Zootaxa, 2023)
Twelve new species of the jumping spider genus Euochin Prószyński, 2018 from southern China are described: Euochin bethunei sp. nov. (♂ ♀), E. buziji sp. nov. (♂ ♀), E. dongpo sp. nov. (♂ ♀), E. extraculum sp. nov. (♂ ♀), E. lingyi sp. nov. (♂ ♀), E. nanjiabawa sp. nov. (♂ ♀), E. nu sp. nov. (♂ ♀), E. shenjun sp. nov. (♂ ♀), E. tianhe sp. nov. (♂ ♀), E. wanlessi sp. nov. (♂ ♀), E. yangmei sp. nov. (♂ ♀), E. zegangi sp. nov. (♂ ♀). Two new combinations are proposed: Euochin bamianshanensis (Liu, Wang & Peng, 2020) comb. nov. and Euochin longyangensis (Lei & Peng, 2012) comb. nov. (both transferred from Euophrys C. L. Koch, 1834, with redescription and revision of male and female pairing provided for the latter). Diagnostic illustrations and photographs are provided.